2019
DOI: 10.3390/cells9010052
|View full text |Cite
|
Sign up to set email alerts
|

The Good, the Bad and the Unknown of CD38 in the Metabolic Microenvironment and Immune Cell Functionality of Solid Tumors

Abstract: The regulation of the immune microenvironment within solid tumors has received increasing attention with the development and clinical success of immune checkpoint blockade therapies, such as those that target the PD-1/PD-L1 axis. The metabolic microenvironment within solid tumors has proven to be an important regulator of both the natural suppression of immune cell functionality and the de novo or acquired resistance to immunotherapy. Enzymatic proteins that generate immunosuppressive metabolites like adenosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 123 publications
(161 reference statements)
1
57
0
Order By: Relevance
“…Moreover, the anti-CD38 therapy approached its therapeutic goals with acceptable adverse effects in patients with multiple myeloma [34][35][36]. The co-inhibition of CD38 and PD-L1 was supposed to treat solid tumor [6]. Our study found that the expression of CD38 was negatively correlated with PD-L1 expression in tumor cells and positively correlated with the PD-L1 expression in immune cells in patients without perigastric lymph node metastasis.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Moreover, the anti-CD38 therapy approached its therapeutic goals with acceptable adverse effects in patients with multiple myeloma [34][35][36]. The co-inhibition of CD38 and PD-L1 was supposed to treat solid tumor [6]. Our study found that the expression of CD38 was negatively correlated with PD-L1 expression in tumor cells and positively correlated with the PD-L1 expression in immune cells in patients without perigastric lymph node metastasis.…”
Section: Discussionmentioning
confidence: 62%
“…Compare to normal cells, though the mRNA and protein expression of CD38 was higher in malignant cells of breast cancer, lung cancer, hepatic cancer and esophageal cancer, and CD38 has been linked to the tumor differentiation, invasion and metastasis, CD38 might exhibit both stimulating and inhibiting effects to tumor development [8,[16][17][18][19]. The function of CD38 was dependent on the cancer type, tumor cell type and interaction with immune cells in the microenvironment [6,8]. CD38 converts NAD + to ADP − ribose (ADPR) and cADPR, which are essential for regulating extracellular metabolites, intracellular Ca2 + level, cell adhesion, and signal transduction pathways [20].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Supporting this, the combination of PARP inhibitors and Nampt inhibitors was shown to induce synthetic lethality in breast cancer cells [140]. The roles of Nampt and NAD + metabolism in metabolic diseases such as cancers and diabetes have been extensively discussed in several recent reviews [5,6,134,138,[141][142][143]. Here we discuss the roles of NAD + , NAD + biosynthesis enzymes Nmnats and NAD + -dependent sirtuins in select diseases of the nervous system.…”
Section: Nad + and Diseasesmentioning
confidence: 92%